(untitled) (Research, Society and Development, 2021)
Objective: to point out the importance of nuclear medicine for the diagnosis and therapy of COVID-19, in addition to reporting the efficacy of treatment with radioisotopes (sodium pertechnetate and iodine 131) in individuals infected with SARS-CoV-2 causing viral sterility and preventing its mutagenesis and ensuring the absence of adverse reactions. Methodology: This is a review of the narrative-type literature, prepared between June and September 2020, using the following databases: PubMed, SciELO and Lilacs. Thus, there was the inclusion of articles published between 1971 and 2020. Results and Discussion: The use of gamma and neutron radiation for the purpose of eliminating viral pathogens has been extensively researched in American studies, initially focusing on H1N1. The substance of Sodium Pertecnate, suggested in this study, and iodo 131 (designed to act as prevention in the cervical region) have the potential for satisfactory responses in the therapeutic treatment of COVID-19 due to the innocuous, painless and free of any effect methodology therefore, offering greater security to the treatment. Inferring in the replication of the coronavirus through the electrolysis of its fatty structure, since with the sterilization of its RNA molecule there will be no replication. Final Consideration: Based on the effectiveness of this method in sterilization protocols and action on various types of microorganisms, especially other viruses that affect the respiratory system, it is suggested as a safe, low-cost and low-dose radioactivity method for the patient, when used doses similar to those of the diagnostic and therapeutic practice in Nuclear Medicine. It should be noted that the administration protocol must be in accordance with the standard already recommended clinically, with full guarantee of the absence of associated effects. For better clarification, there is a need for more specific research within the scope of SARS-CoV-2.